MITIGATION AND ADAPTATION OF THE IMPACTS OF CLIMATE CHANGE - D.G.Muminov; Z.Ashirov; A.Urinboyeva (Web of Journals Publishing, 2023)
Climate change and its environmental consequences are the main problem of our time. This paper examines the impact of climate change on the Fergana Valley as an example. The consequences of climate change and adaptation to them are discussed.
Keywords: climate, climate change, temperature change, winds, precipitation, environmental problems.